Rahasia Sukses Menuntut Ilmu Pengetahuan (Studi Analisa Pemikiran Imam Ali Karamallahu Wajhahu). - Hikmatuloh, Hikmatuloh (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2022)
Imam Ali Karamallahu Wajhahu, is the cousin of the Prophet Muhammad as well as his son-in-law and one of the 10 (ten) companions of the Prophet who are guaranteed to enter heaven. Among the privileges of Imam Ali Karramallahu Wajhahu is the nickname